Atheism and the changing image of Islam in Iraq - Graczyk, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to present the situation of atheists and apostates in Iraq, as the tendency to abandon religion is increasing in this country. With the fall of the regime of Saddam Hussein and his party, Shiites took power in the country, who, guided by religious doctrine, often limit the freedoms and rights of citizens.
Keywords: Iraq; atheism; apostate; islam; religion; law